Optimalisasi untuk Menurunkan Prevalensi Anemia pada Ibu Hamil Berbasis Kelas Ayah - Yully Asmariana; Rahmania Ambarika (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Maternal Mortality Rate (MMR) remains a priority health issue, with one of the main causes being postpartum hemorrhage, which is closely related to anemia in pregnant women. Iron deficiency anemia is the most common condition experienced by women of reproductive age and has serious impacts on both mother and fetus, including increased risk of morbidity, mortality, premature birth, and low birth weight. Although antenatal care (ANC) and iron supplementation have become standard services, these efforts are not fully optimized without the support of social determinants, particularly husband involvement. Husband support plays a crucial role in improving adherence to iron supplementation, achieving a balanced diet, regular ANC visits, and making informed health decisions during pregnancy. However, husband involvement in maternal health practices remains low due to limited knowledge and participation. Therefore, innovation based on husband empowerment through Father Classes is needed as a supporting strategy to optimize anemia prevention in pregnant women on a sustainable basis. Objective: This activity aims to increase husband involvement through Father Class education on anemia prevention in pregnant women. Method: This community service activity uses an educational design with a pre-posttest approach and is implemented through an institutional partnership between STRADA Indonesia University and UPT. The Singkawang Utara I Community Health Center in Singkawang City, with midwives as the primary partner, was conducted from January 5 to 21, 2026, and involved 29 participants, including husbands of pregnant women, cadres, religious leaders, and community leaders who met the inclusion criteria. The activity included preparation (coordination, permits, and situational analysis), implementation of the Father's Class education, and evaluation through pretest and posttest questionnaires. Data were analyzed quantitatively and descriptively to compare participants' knowledge levels before and after the educational intervention. Results: Measurements showed a significant increase in participants' knowledge after receiving the Father's Class education. The average knowledge score on anemia prevention in pregnant women increased from 14.72 ± 17.01 in the pretest to 85.14 ± 5.55 in the posttest, with a p-value of 0.000. These results indicate that the educational intervention was effective in increasing participants' understanding of anemia prevention, including the importance of taking iron supplements, achieving a balanced diet, and the active role of husbands in supporting the health of pregnant women. This increased knowledge is expected to form the basis for changes in husbands' attitudes and behaviors regarding their involvement in supporting their wives during pregnancy, particularly in anemia prevention. Conclusion: Community service activities through the Fathers' Class education program have proven effective in increasing husbands' knowledge regarding anemia prevention in pregnant women. The significant increase in knowledge after the intervention indicates that husbands' involvement through an educational approach can be an important supporting strategy in improving adherence to iron supplementation, achieving balanced nutrition, and preventing high-risk pregnancies. Therefore, the implementation of the Fathers' Class program has the potential to become a sustainable intervention model and can be integrated into maternal health services at the community health center level to reduce the prevalence of anemia.